1989
DOI: 10.1577/1548-8659(1989)118<0368:cicafo>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Characteristics and Function of Woody Debris with Increasing Size of Streams in Western Washington

Abstract: In second‐ to fifth‐order streams that drain old‐growth timber in western Washington, characteristics and function of woody debris changed in relation to stream size. Average diameter, length, and volume of pieces of wood increased as stream size increased, whereas the frequency of occurrence of woody debris decreased. In streams with channel widths less than 7 m, 40% of the pieces of debris were oriented perpendicularly to the axis of flow; in streams with channel widths over 7 m, more than 40% of the pieces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
248
6
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(278 citation statements)
references
References 3 publications
18
248
6
3
Order By: Relevance
“…These elements provide heterogeneity of light intensities and hydraulic variables among microhabitats and within mesohabitat units but can also be involved in the distribution pattern of mesohabitat units (SHIELDS JR and SMITH, 1992;ABBE and MONTGOMERY, 1996;GIPPEL et al, 1996). For example, woody debris may contribute to geomorphic processes such as step-pool profile formation, waterfall formation, initiation of vegetated islets on gravel bars, or backwater formation (BILBY and WARD, 1989;ROBISON and BESCHTA, 1990;GURNELL et al, 1995;RICHMOND and FAUSCH, 1995). By increasing the diversity of the stream bed, trapping gravel, and creating shallow gravel bars, woody debris or stream enhancement structures are used to increase spawning habitat for salmonids (HOUSE and BOEHNE, 1985).…”
Section: Effects Of Cover Structures On Habitat Featuresmentioning
confidence: 99%
“…These elements provide heterogeneity of light intensities and hydraulic variables among microhabitats and within mesohabitat units but can also be involved in the distribution pattern of mesohabitat units (SHIELDS JR and SMITH, 1992;ABBE and MONTGOMERY, 1996;GIPPEL et al, 1996). For example, woody debris may contribute to geomorphic processes such as step-pool profile formation, waterfall formation, initiation of vegetated islets on gravel bars, or backwater formation (BILBY and WARD, 1989;ROBISON and BESCHTA, 1990;GURNELL et al, 1995;RICHMOND and FAUSCH, 1995). By increasing the diversity of the stream bed, trapping gravel, and creating shallow gravel bars, woody debris or stream enhancement structures are used to increase spawning habitat for salmonids (HOUSE and BOEHNE, 1985).…”
Section: Effects Of Cover Structures On Habitat Featuresmentioning
confidence: 99%
“…As large wood travels downstream, the biological and physical processes begin to fragment and decay of wood pieces (Bilby and Ward, 1989). The processes of fragmentation and decay reduce the total amount of the large wood in the longitudinal dimension; however, the actual rate per downstream distance is unclear, being complicated by a number of factors including physical hydraulic forces, biotic decay rates, and residence time.…”
Section: Explanation 4 -Significant Fragmentation/decaymentioning
confidence: 99%
“…One general pattern to emerge from field and flume studies is that large wood movement is affected by the ratio of piece-size to channel-width and is dependent on the specific channel morphology of a river reach (Lienkaemper and Swanson, 1987;Bilby and Ward, 1989;Nakamura and Swanson, 1994;Braudrick and Grant, 2000). These studies found that smaller wood pieces move more frequently through larger streams that have a Fremier, Page 6 of 39 higher capacity to move larger pieces of wood; however, it has been observed that some pieces are too large or anchored by the bank that transport does not occur even at high flows (Piégay et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In forested streams, woody debris provides a physical retention mechanism, controlling and reducing the extent of downstream movement of organic and inorganic material (Keller & Swanson 1979;Mosley 1981;Bilby & Ward 1989). Woody debris dams are important storage sites of organic material in the stream, increasing the time available for biological processing before the organic material is transported further down stream (Bilby & Likens 1980;Cummins et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant species is Pinus radiata which makes up 91% of the total planted area (NZFOA 1997). Little data is available on the amount and distribution of woody debris in pine plantation streams, particularly in the small first-to third-order streams, where woody debris has the most influence on stream dynamics (Harmon et al 1986;Sedell et al 1988;Bilby & Ward 1989). Woody debris characteristics have been measured by: Evans et al ( 1993b) in two streams in 10-year-old pine plantations; Quinn et al (1997), in three streams of 15-year-old pine plantations; and Collier et al (1998) in three streams in mature and recently harvested pine plantations in New Zealand.…”
Section: Introductionmentioning
confidence: 99%